Integrasi Sistem Informasi Manajemen Dan Business Intelligence Untuk Mendukung Strategi Bisnis - B.R.E. Yunanda; Abdullah, Aprizal Rahmat; Adia Sarifah; Netha Ardina (Lembaga Pengembangan Kinerja Dosen, 2025)
In the digital era, data has become a strategic asset that greatly determines business success. Management Information Systems (MIS) have been widely used for recording operational data, but have not been fully able to provide analytical support for strategic decision making. Business Intelligence (BI) is present as a complementary solution to process data into strategically valuable information. This article discusses the integration of MIS and BI in the context of increasing the effectiveness of business strategies, with a case study on retail sector MSMEs. The research method uses a qualitative descriptive approach, involving observation, interviews, and documentation. The system is designed web-based with MIS modules and BI dashboards using Google Data Studio. The implementation results show increased operational efficiency, data accuracy, and strategic analysis capabilities. This research contributes to the development of integrated information systems to support the competitive advantage of small and medium-sized businesses.